Forms of Organizing Collective Educational Activity at Primary School. (5th December 2015) - Pozdeeva, Svetlana; Plotnikova, Natalia
Abstract: Adopting an activity approach, with the teachers and learners as co-participants, the study focuses on the process of English teaching at modern primary school, examining forms of organizing collective educational activity. Authors explain how teaching of English via different stages and collective forms is organized at modern primary school. Collective educational activity is associated with communicative and cognitive development of a child and professional and personal development of a teacher. According to the Federal State Educational Standard of primary general education, the subject, metasubject and personal results of education are presented in the paper. Research stages and results of using different forms of educational activity, such as group working are described. The most effective forms of educational activity are scheme «CCS» (Collect – Comprehend – Systematize) observation, training on stations and others. It is proved that the main educational result in teaching a foreign language at primary school is the formation of universal communication training activities.